Head-to-head comparison of SARS-CoV-2 antigen-detecting rapid test with self-collected anterior nasal swab versus professional-collected nasopharyngeal swab - Lindner, Andreas; Nikolai, Olga; Kausch, Franka; Wintel, Mia; Hommes, Franziska; Gertler, Maximilian; Krüger, Lisa; Gaeddert, Mary; Tobian, Frank; Lainati, Federica; Köppel, Lisa; Seybold, Joachim; et al. (The European respiratory journal, 2021)
A number of antigen-detecting rapid diagnostic tests (Ag-RDTs) for SARS-CoV-2 are now commercially available and can result in rapid decisions on patient care, isolation and contact tracing at the point-of-care [1]. Two Ag-RDTs using nasopharyngeal (NP) swab samples meet WHO targets and are now approved through the WHO Emergency Use Listing procedure [2-4]. - - Heike Rössig, Chiara Manon Rohardt, Claudia Hülso, Elisabeth Linzbach, Susen Burock, Katja von dem Busche, Stephanie Padberg, Melanie Bothmann, Zümrüt Tuncer, Stefanie Lunow, Beate Zimmer, Astrid Barrera Pesek, Sabrina Pein, Nicole Buchholz, Verena Haack, Oliver Deckwart.
Previous version: December 10, 2020
Gesehen am 15.12.2020